Steam sauna and mother roasting in Lao PDR: practices and chemical constituents of essential oils of plant species used in postpartum recovery - de Boer Hugo J; Lamxay Vichith; Björk Lars (BMC, 2011)
Abstract Background Fundamental in traditional postpartum recovery in Lao PDR is the use of hotbeds, mother roasting, steam sauna and steam baths. During these treatments medicinal plants play a crucial role, but little has been published about how the treatments are carried out precisely, which species are used, the medicinal properties of these species, and the medicinal efficacy of their chemical constituents. Methods Sixty-five interviews, in 15 rural villages, with women of 4 different ethnic groups were conducted to survey confinement rituals, and postpartum plant use and salience. Essential oils from the main species used were extracted using steam distillation and the main chemical constituents characterized using gas chromatography-mass spectrometry (GC-MS). Results A total of 10 different species were used by three or more of the ethnic groups included in this study. All species were used in steam sauna and bath, but only 3 species were used in hotbed and mother roasting. Essential oils of Amomum villosum, Amomum microcarpum and Blumea balsamifera were found to contain significant amounts of the following terpenes: β-pinene, camphor, bornyl acetate, borneol, linalool, D-limonene, fenchone, terpinen-4-ol and α-terpinene. Conclusions Many of these terpenes have documented antimicrobial and analgesic properties, and some have also synergistic interactions with other terpenes. The mode of application in hotbed and mother roasting differs from the documented mechanisms of action of these terpenes. Plants in these two practices are likely to serve mainly hygienic purposes, by segregating the mother from infection sources such as beds, mats, stools, cloth and towels. Steam sauna medicinal plant use through inhalation of essential oils vapors can possibly have medicinal efficacy, but is unlikely to alleviate the ailments commonly encountered during postpartum convalescence. Steam sauna medicinal plant use through dermal condensation of essential oils, and steam bath cleansing of the perineal area is possibly a pragmatic use of the reported medicinal plants, as terpene constituents have documented antimicrobial, analgesic and anti-inflammatory properties.